2021
DOI: 10.1002/aah.10139
|View full text |Cite
|
Sign up to set email alerts
|

Farm‐Level Cost Drivers of Salmonid Fish Health Inspections

Abstract: Regulatory costs on aquaculture farms have been shown to be of a magnitude that warrants additional analysis. The drivers of farm-level costs of fish health inspections were identified in this study from national survey data on U.S. salmonid farms. The greatest costs identified were related primarily to state fish health requirements for inspection and testing to certify that fish are free of specific pathogens prior to approval of necessary permits to sell and/or transport animals. Fish health inspection cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Environmental regulations and fish health testing contributed significantly to the regulatory costs and value of lost production in the salmonid and sportfish/baitfish industries. Fish health testing costs were especially onerous on farms selling into sportfishing markets either for bait (van Senten & Engle, 2017) or for recreational fishing (Engle et al, 2021). Conversely, in the ornamental industry where farms tend to be smaller in scale and sell products to non-food markets, regulatory burdens have indirect production effects in the areas of restricted drugs and chemicals, predator control, and prohibited species.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental regulations and fish health testing contributed significantly to the regulatory costs and value of lost production in the salmonid and sportfish/baitfish industries. Fish health testing costs were especially onerous on farms selling into sportfishing markets either for bait (van Senten & Engle, 2017) or for recreational fishing (Engle et al, 2021). Conversely, in the ornamental industry where farms tend to be smaller in scale and sell products to non-food markets, regulatory burdens have indirect production effects in the areas of restricted drugs and chemicals, predator control, and prohibited species.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies point to opportunities with regard to specific types of potentially useful regulatory reforms. For example, van Senten, Engle, et al (2018) and Engle, van Senten, et al (2021) found that risk‐based approaches to fish health testing required for interstate movement of live fish had potential for substantial reductions in on‐farm compliance costs. Boldt et al (2022) found that regulatory reforms that resulted in improved access to restricted drugs and chemicals for non‐foodfish species and use of risk‐based approaches to managing approvals of non‐native species in aquaculture would reduce negative impacts to US aquaculture farms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the baitfish/sportfish farms, a 10% reduction in the cost of manpower spent on regulatory compliance alone could increase the technical efficiency of farms from 77% to 78% (van Senten, Dey, & Engle, 2018; van Senten, Engle, et al, 2018). Fish health testing costs required for sales into other states could be reduced through risk‐based approaches as compared with current practices (Engle, van Senten, et al, 2021). Adopting uniform health standards for aquaculture was estimated to save $6.6 million annually to the US baitfish/sportfish industry (van Senten, Dey, & Engle, 2018; van Senten, Engle, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the regulatory framework as implemented has resulted in inefficiencies on farms (van Senten, Dey, & Engle, 2018). Innovative approaches to regulating aquaculture have been shown to have potential to achieve equivalent oversight at lower cost (Engle, van Senten, Schwarz, Hartman, et al, 2021; van Senten, Engle, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%